AL-WAHN LI MUWAJAHAT AL-IHTILAL FI QASHIDAT “YA QUDSU MAʿDZIRATAN” LI AHMAD MATHAR - Alam An Shori; Maulana Muhammad Fikri; Halimi Zuhdy; Aulia Fadhila Wirmansyah (Afshaha: Jurnal Bahasa dan Sastra Arab, 2024)
The poem Ya Qudsu Maʿḏirotan relates to Israel's occupation of the land of Jerusalem. The researchers wants to analyse this poem to find out the ideology in this poem. The type of this research is qualitative research using Norman Fairclough's Critical Discourse Analysis. The data collection technique is reading and writing. The researchers read Ahmed Matar's poem Ya Qudsu Maʿḏirotan and then wrote down the data from the poem. The researchers used a data analysis technique using Norman Fairclough's CDA, which has three dimensions: the textual dimension, the discourse practice dimension, and the sociocultural practice dimension. In the textual dimension, the researchers analysed Ahmed Matar's poem Ya Qudsu Maʿḏirotan in terms of linguistics. In the discourse practice dimension, the researchers analysed the process of production and consumption of this poem. And in the sociocultural practice, the researchers analysed the social context of this poem. The conclusion about ideology of this research is that one of the factors of the ongoing occupation of Jerusalem is the weakness of the Arab leaders through the poet's criticism of the weakness of the Arab leaders to liberate the land of Jerusalem.